2014
DOI: 10.1111/1753-6405.12257
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic differences in outdoor food advertising at public transit stops across Melbourne suburbs

Abstract: Objective: To assess and compare the number and type of outdoor food advertisements at public transit stops within suburbs of varying levels of socioeconomic disadvantage.Method: An observational audit tool was developed and implemented to assess the number and type of food advertisements at public transit stops within Melbourne, Victoria. A total of 20 Melbourne neighbourhoods (suburbs) from across the least and the most socioeconomically disadvantaged areas were selected. All public transit stops, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 25 publications
1
39
1
5
Order By: Relevance
“…Settle et al reported a similar product breakdown in their audit of Melbourne public transit stops, supporting the transferability of our results to the broader Australian context [32]. The lower volume of advertisements for water-based sugar-sweetened beverages appears promising, given the evidence identifying high intakes of soft-drinks as a probable causal factor in weight gain [5].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Settle et al reported a similar product breakdown in their audit of Melbourne public transit stops, supporting the transferability of our results to the broader Australian context [32]. The lower volume of advertisements for water-based sugar-sweetened beverages appears promising, given the evidence identifying high intakes of soft-drinks as a probable causal factor in weight gain [5].…”
Section: Discussionsupporting
confidence: 76%
“…Kelly and colleagues investigated food and beverage advertising surrounding primary schools in New South Wales (NSW) and identified train stations as the setting with the highest proportion of non-core food advertising (90%) [31]. Recent studies investigating advertising at Melbourne [32], Sydney [33] and Perth [34] transit stops reported a high proportion of advertising for snack foods, sugar-sweetened and intense-sweetened beverages, and alcohol. Settle and colleagues [32] found that 30% of sampled transit stops in Melbourne displayed food advertisements, with some variation between the types of food and beverages advertised according to the level of socioeconomic disadvantage of the suburb.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Grier and Kumanyika 2008;Isgor et al 2016;Powell et al 2014;Settle et al 2014). Therefore, it is equally possible that companies strategically target the development of new unhealthy outlets in lower socioeconomic neighbourhoods.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…Research from the USA has indicated that areas of greater socio‐economic disadvantage are more likely to have a higher number of outdoor alcohol advertisements than areas of socio‐economic advantage . Previous audits of bus stop advertisements in Perth's inner city have recorded a much higher volume of alcohol promotions, and recent audits of advertisements on public transport infrastructure in other Australian capital cities have similarly yielded a larger proportion of alcohol promotions . However, given the harms associated with alcohol consumption among young people, the placement of any alcohol advertising near schools is inconsistent with policy recommendations from leading health and medical organisations…”
Section: Discussionmentioning
confidence: 99%